Arabic visual dictionary - Fakhouri, Shoua; Nasr, Imad; Reid, Lauren (Collins, 2019)
The home of trusted full-colour visual dictionaries for everyday use. A photographic guide to the key words and phrases in Arabic. This attractive pocket-sized book is a perfect travel companion and provides a practical guide to the Arabic language, world and culture.